Effect of Co-administration of Bumetanide and Phenobarbital on Seizure Attacks in Temporal Lobe Epilepsy - Reza Rahmanzadeh; Soraya Mehrabi; Mahmood Barati; Milad Ahmadi; Fereshteh Golab; Sareh Kazmi; Mohammad Taghi Joghataei; Morteza Seifi; Mazaher Gholipourmalekabadi (Basic and Clinical Neuroscience, 2018)
Introduction: The resistance of temporal lobe epilepsy to classic drugs is thought to be due to disruption in the excitation/inhibition of this pathway. Two chloride transporters, NKCC1 and KCC2, are expressed differently for the excitatory state of Gamma-Amino Butyric Acid (GABA). The present study explored the effect of bumetanide as a selective NKCC1 inhibitor either alone or in combination with the phenobarbital in the pilocarpine model of epilepsy. Methods: An animal model of Status Epilepticus (SE) was induced with pilocarpine in Wistar male rats followed by phenobarbital and or bumetanide or saline administration for 45 days after the induction of SE by Intraperitoneal (IP) injection. The rats were monitored, their behavior was recorded, and after 24 hours they were sacrificed to study the expression of NKCC1 and KCC2 using real time PCR. Results: The data showed that the effects of a combination of bumetanide with phenobarbital on frequency rate and duration of seizure attack were more than those of the phenobarbital alone. In addition, in the bumetanide and combined treatment groups, NKCC1 expression decreased significantly, compared with untreated epileptic animals. A delayed decrement in NKCC1/KCC2 expression ratio after bumetanide application was also observed. Conclusion: The combination of bumetanide with phenobarbital increases the inhibition of SE and maximizes the potential of GABA signaling pathway, and can be considered as an effective therapeutic strategy in patients with epilepsy.